2021
DOI: 10.1038/s41598-021-85147-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Fe-acquisition genes causing decreased Fe uptake and photosynthetic inefficiency in Fe-deficient sunflower

Abstract: Iron (Fe) deficiency in plants hinders growth and yield. Thus, this study aims to elucidate the responses and molecular characterization of genes in Fe-deficient sunflower. The study was conducted on 14 days-old sunflower plants cultivated in hydroponic culture under Fe-sufficient and Fe-deficient conditions. The Fe-starved sunflower showed substantial decrease in plant biomass, SPAD score, quantum yield efficiency of PSII (Fv/Fm), photosynthetic performance index (Pi_ABS). Further, Fe shortage reduced Fe and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…These data suggest that Fe stress decreases the photochemical capacity and Chl per unit area accompanied by a reduction in the number of grana and stroma lamellae per chloroplast and by a reduction in the number of thylakoids per granum (Dorta‐Santos et al, 2020; Elkhouni et al, 2018; Osório et al, 2014). Kabir et al (2021) described that Fe shortage reduced Fe and Zn concentrations in roots and shoots, accompanied by a marked decrease of HaNramp1 and HaZIP1 expression in roots, suggesting the association of Zn status contributing to photosynthetic inefficiency.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that Fe stress decreases the photochemical capacity and Chl per unit area accompanied by a reduction in the number of grana and stroma lamellae per chloroplast and by a reduction in the number of thylakoids per granum (Dorta‐Santos et al, 2020; Elkhouni et al, 2018; Osório et al, 2014). Kabir et al (2021) described that Fe shortage reduced Fe and Zn concentrations in roots and shoots, accompanied by a marked decrease of HaNramp1 and HaZIP1 expression in roots, suggesting the association of Zn status contributing to photosynthetic inefficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The LsZIP gene family contains cis-acting elements that respond to hormones and stress, such as methyl jasmonate, abscisic acid, auxin, and salicylic acid. In a previous study, Akther [ 48 ] found that tolerance to Zn deficiency in tomato is dependent on auxin signaling; Song [ 49 ] found that ABA can reduce Zn uptake and accumulation in grapes by inducing ZIP gene expression; furthermore, Kabir [ 50 ] found that salicylate and methyl jasmonate response elements in three ZIP genes of sunflower were regulated in response to iron deficiency; Matsuoka [ 51 ] found that erythromycin positively regulated AtZIP1 expression under iron sufficiency or iron deficiency conditions. This suggests that LsZIP gene expression may be induced by several plant hormones, such as salicylic acid, MeJA, abscisic acid, gibberellin, and auxin.…”
Section: Discussionmentioning
confidence: 99%
“…The ROS otherwise would be an inducer for different genes related to Al tolerance most specifically synthesis of organic acids. The organic acids in turn are also induced by some growth regulators like ethylene under Al stress [141] Ethylene in wheat has also been reported with negative control for Al activated malate transporter (ALMT1) that reduces the root secretion of organic acids. Thereby, mutation of this gene would be sufficient for sensitive to Al toxicity [142].…”
Section: Phytohormone Signaling and Functioning For Aluminum Tolerancementioning
confidence: 99%